Legal Protection For Heirs Of Land Deeds Which Only Use The Name Of Their First Child In The Perspective Of Islamic Inheritance Law and Civil Law - Fitriyan Ferdi Nastopa (International Significance of Notary, 2023)
This study is entitled Legal Protection for Heirs of Land Deeds Using Only the Name of the First Child in the Perspective of Islamic Inheritance Law and Civil Law.There are two formulations of the problem. 1 (one) What is the status of the heirs' rights to the land deed that only uses the name of their first child? 2 (Two) How is the legal protection of heirs for land deeds that only use the name of their first child from the perspective of Islamic inheritance law and civil law? The type of research used is normative juridical, namely research that refers to legal norms contained in statutory regulations. The nature of the research is analytical descriptive through a statute approach. The results of this study, the status of heirs' rights to land deeds that only use the name of their first child is that in principle all heirs are entitled to an equal share of inheritance, regardless of gender. So even though the land deed only uses the name of the first child, the other heirs are still entitled to receive inheritance from the heir. is in the form of good faith among heirs in the implementation of an application for determination of heirs, on the one hand to seek justice, on the other hand, to determine who will become the heir, to determine the inheritance, to determine the share of each heir, and to carry out the distribution of the inheritance. the second is repressive legal protection aimed at resolving disputes. In this study, the cancellation of the deed, with the aim that when there is a dispute or physical possession of property controlled by one of the heirs on the pretext that he has a deed given by his parents on his behalf, then the deed must be canceled, with the aim that the other heirs do not someone is harmed.  Keywords: Legal Protection, Land Deed, Inheritance